Blockade of IL-33R/ST2 Signaling Attenuates Toxoplasma gondii Ileitis Depending on IL-22 Expression - Ryffel, Bernhard; Huang, Feng; Robinet, Pauline; Panek, Corine; Couillin, Isabelle; Erard, François; Piotet, Julie; Le Bert, Marc; Mackowiak, Claire; Torres Arias, Marbel; Dimier-Poisson, Isabelle; Zheng, Song Guo (Frontiers in Immunology, 2019)
Oral T. gondii infection (30 cysts of 76K strain) induces acute lethal ileitis in sensitive C57BL/6 (B6) mice with increased expression of IL-33 and its receptor ST2 in the ileum. Here we show that IL-33 is involved in ileitis, since absence of IL-33R/ST2 attenuated neutrophilic inflammation and Th1 cytokines upon T. gondii infection with enhanced survival. Blockade of ST2 by neutralizing ST2 antibody in B6 mice conferred partial protection, while rmIL-33 aggravated ileitis. Since IL-22 expression further increased in absence of ST2, we blocked IL-22 by neutralizing antibody, which abrogated protection from acute ileitis in ST2 deficient mice. In conclusion, severe lethal ileitis induced by oral T. gondii infection is attenuated by blockade of ST2 signaling and may be mediated in part by endogenous IL-22.